Engaging Young Learners to Study English Through Storytelling Using E-Storybook - Pujiani, Tri; Zuhrufillah, Irfani; Sukmawati, Ida Dian; Yani, Riski Fitri (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2022)
Teaching English to young learners is somehow challenging. They have unique characteristics such as being very active, easily getting bored and being distracted. The teachers are required to be creative in designing the lesson. Storytelling can be a powerful technique in teaching language to young learners. With the advance in digital technology, an e-storybook offers a new experience of a reading story. It offers opportunities to enjoy animations, hear and follow along with text using the read-aloud feature, and engage with interactive options to support active readers. This study aimed to find out the effectiveness of the storytelling technique using e-storybook in increasing young learners' learning engagement in English class. This study was a case study conducted in a kindergarten in Purwokerto. The data was collected through observation and interviews. The finding revealed that the students displayed higher enthusiasm during the storytelling activity. Moreover, the use of an e-storybook enabled the students re-read the story independently and actively control their reading pace to increase their understanding. The result of the study showed an increase in students' vocabulary mastery, text comprehension, and retelling skills. This study concludes that storytelling using an e-storybook is effective to improve young learners' engagement in English class. It is expected that the result of this study may give insight into teaching English to young learners practice.